THE INFLUENCE OF MONETARY POLICY ON INVESTMENT DECISION IN THE EURO ZONE - Valentin Mihai LEOVEANU; Anca BRATU (Challenges of the Knowledge Society)
The paper aims to highlight and analyze the main theoretical and practical aspects regarding the relationship between investment and monetary policy, as monetary policy decisions had a greater or lesser relevance on investment decisions. First, the authors make a short review into the theoretical analysis of interconnections between money and investments, and then they try to reveal how the monetary policy influences the investment decisions through the transmission mechanism channels. The effect of monetary policy measures on investment decision is followed by the authors on three levels of analysis: the selection of investment projects, the choice of sources of financing and the measurement of risk.